Esfera pública e meio ambiente - Cava, Roberta (2011)
The advance of techonologies, especially the mass communication means, had approached not only the world economies, but also cultures and societies. The emergency of a called global society brings the coletivities together, and throws them into planetary orbit. It promotes a redefinition of the Nation-State and, consequently, a reflection of the traditional public sphere concept. Observing the new amplitude of communicational flows allows to observe the rising of civil society on international scenary. Its space for deliberation is related to comprehensions of international dinamic, as well to the human relations transcending national frontiers. National movements point out the recognizement of the transversality of human interests, marked by world public opinion tendencies, tied to the informational growth and the globalization process. This research intends to approach Jürgen Habermas public sphere traditional concept, revisited in a transnational dimension, once themes previously belonging to national agendas move to world agenda, establishing commom concerns, as environment and climate change.